Best practices of human resource management at brazil's top universities: Case studies - Freitas, Wesley Ricardo Souza [UNESP]; Jabbour, Charbel José Chiappetta; De Castro, Rosani [UNESP] (My University, 2011)
The objective of this study is to identify and verify how the best practices of human resource management are being developed at three of the most prestigious public universities in Brazil located in the state of São Paulo (USP, UNESP and UNICAMP), focusing on administrative employees. It can be concluded, that these universities are at relatively different levels of human resource management. This could be justified by the decentralization policy at UNESP (more than 20 campuses) and USP (seven campuses), since they are present in several cities in the state of Sao Paulo that are geographically dispersed. As a result, these campuses have great autonomy to develop actions, different from UNICAMP, which concentrates most of its units and colleges at the same campus. © EuroJournals Publishing, Inc. 2011.
Keywords: Brazil; Higher Education; Human Resource Management; Universities